Integrated (one‐stop shop) youth health care: best available evidence and future directions. (20th November 2017) - Hetrick, Sarah E; Bailey, Alan P; Smith, Kirsten E; Malla, Ashok; Mathias, Steve; Singh, Swaran P; O'Reilly, Aileen; Verma, Swapna K; Benoit, Laelia; Fleming, Theresa M; Moro, Marie Rose; Rickwood, Debra J; et al.
Summary: Although mental health problems represent the largest burden of disease in young people, access to mental health care has been poor for this group. Integrated youth health care services have been proposed as an innovative solution. Integrated care joins up physical health, mental health and social care services, ideally in one location, so that a young person receives holistic care in a coordinated way. It can be implemented in a range of ways. A review of the available literature identified a range of studies reporting the results of evaluation research into integrated care services. The best available data indicate that many young people who may not otherwise have sought help are accessing these mental health services, and there are promising outcomes for most in terms of symptomatic and functional recovery. Where evaluated, young people report having benefited from and being highly satisfied with these services. Some young people, such as those with more severe presenting symptoms and those who received fewer treatment sessions, have failed to benefit, indicating a need for further integration with more specialist care. Efforts are underway to articulate the standards and core features to which integrated care services should adhere, as well as to further evaluate outcomes. This will guide the ongoing development of best practice models of service delivery.